The effect of prophylactic dexmedetomidine on hemodynamic disturbances to double-lumen endotracheal intubation: A prospective, randomized, double-blind, and placebo-controlled trial - Pipanmekaporn T. (2014)
The purpose of this study was to determine the effect of dexmedetomidine on hemodynamic responses to DLT intubation compared to placebo and to assess the adverse effects related to dexmedetomidine. Sixty patients were randomly allocated to receive 0.7 g/kg dexmedetomidine (n=30) or normal saline (n=30) 10 minutes before general anesthesia. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR), and rate pressure product (RPP) between groups were recorded. During intubation and 10 minutes afterward (T1-T10), the mean SBP, DBP, MAP, HR, and RPP in the control group were significantly higher than those in the dexmedetomidine group throughout the study period except at T1. The mean differences of SBP, DBP, MAP, HR, and RPP were significantly higher in the control group, with the value of 15.2 mmHg, 10.5 mmHg, 14 mmHg, 10.5 beats per minute, and 2,462.8 mmHg min -1. Four patients in the dexmedetomidine group and 1 patient in the control group developed hypotension, while 2 patients in the dexmedetomidine group had bradycardia. Prophylactic dexmedetomidine can attenuate the hemodynamic responses to laryngoscopy and DLT intubation with minimal adverse effects. This trial is registered with ClinicalTrials.gov NCT01289769. © 2013 Tanyong Pipanmekaporn et al.